Knee strengthening exercises at home, but not dietary intervention, reduce knee pain and improve knee function in overweight and obese people over 2 years. Issue 1 (22nd February 2010) - Messier, Stephen P
Abstract : Commentary on: Jenkinson CM Doherty M Avery AJ . Effects of dietary intervention and quadriceps strengthening exercises on pain and function in overweight people with knee pain: randomised controlled trial . BMJ 2009 ;339 :b3170 .